Implementasi Kebijakan Pelayanan Kesehatan Masyarakat Di RSUD dr. R. Koesma Kabupaten Tuban - Nurhuda Firmansyah (Program Studi Doktor Ilmu Administrasi, FISIP, Universitas 17 Agustus 1945 Surabaya, 2014)
Healthcare is the service delivery intangible nature, by therefore measurement of health care costs in no quite simply using size - only financial measures but must also using size - non-financial measures. Along with increasingly society demands against cause community health services become more hearts selectively choose services of a hospital. In Tuban, health facilities in the last 5 years been progressing well. A number of health care facilities, both public and private spread in various corners in the district of Tuban. But unfortunately, it has not been accompanied with good service quality. Yet many people who complain of health services. The complaint include related health services that are less professional, less complete laboratory facilities, supply drugs that are not qualified and indications misdiagnosis in patients. Of these issues, it is still traumatized society. This research is a qualitative descriptive study, conducted in dr. R. Koesma Tuban hospital using qualitative data analysis techniques to the steps of data reduction, data display and conclusion. Supporting factors in this study is the socialization of health care programs, facilities and infrastructure, and has authority in the organization of medical services and medical and non-medical support. While the limiting factor is no gap between the provision of incentives for civil servants and non-civil employees, there are officers who provide health services does not match SOP. Suggestions from this research is to recruit new personnel or skill improvement through training for human resources in dr. R. Koesma hospital to the needs of the specialist personnel, improve the management of hospital budgets in order to be able to finance it’s operations, as well as to improve the welfare of its employes, as well as effective communication training to be more professional in serving patients.Keywords: Implementation, Policy, Health Service